1982
DOI: 10.1093/infdis/146.4.479
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and Growth of Coagulase-Negative Staphylococci on Surfaces of Intravenous Catheters

Abstract: Colonization of intravenous catheters by coagulase-negative staphylococci was followed by scanning electron microscopy. Regular sampling of specimens demonstrated adhesion of the staphylococci to the catheter surface followed by cell proliferation, possible breakdown of catheter components, and production of a slimy material covering the bacterial colonies. The implications of these findings with reference to nosocomial infections of prosthetic devices are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
229
2
15

Year Published

1983
1983
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 549 publications
(252 citation statements)
references
References 1 publication
6
229
2
15
Order By: Relevance
“…In relation to the distribution of slimeproducing species of clinical source, the results are similar to those reported by other authors (8,27), who found that S. epidermidis frequently infects biomedical implants like intravascular catheters and prosthetic valves. It has also been reported (4,24) that most of the isolates of this species from such devices produce a great quantity of extracellular mucoid substance or slime, which was also detected in this study.…”
Section: Discussionsupporting
confidence: 87%
“…In relation to the distribution of slimeproducing species of clinical source, the results are similar to those reported by other authors (8,27), who found that S. epidermidis frequently infects biomedical implants like intravascular catheters and prosthetic valves. It has also been reported (4,24) that most of the isolates of this species from such devices produce a great quantity of extracellular mucoid substance or slime, which was also detected in this study.…”
Section: Discussionsupporting
confidence: 87%
“…Although rapid detection of S. aureus in clinical specimens is essential for appropriate patient care, the recovery and identification of other staphylococci is also important, especially from catheters and other foreign-body samples and blood cultures (16)(17)(18)(19)(20)(21). Culture-based detection methods are cost-effective and useful, especially when various microbe species are examined.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, surface defects may be secondary to microbial colonisation. This theory is supported by reports that some strains of S. epidermidis may cause erosion of the surface of a variety of cannula types, including those made of Teflon (Peters et al, 1982).…”
Section: Discussionmentioning
confidence: 71%
“…Recent in-vitro studies have suggested that surface defects in the cannulae favour bacterial attachment and subsequent colonisation (Locci,Peters and Pulverer,198 lb). The production of slime and the breakdown of catheter components by bacteria may promote such colonisation (Peters, Locci and Pulverer, 1982). Moreover, it has been shown that intravenous cannulae provoke a tissue response that results in the formation of a fibrin sleeve around the cannula (Hoshal, Ause and Hoskins, 1971).…”
Section: Introductionmentioning
confidence: 99%